An Exploratory Study on Critical Factors Affecting Work-Life Balance among Academicians: A Case Study - Othman, Siti Fatihah Che; Zulkifli, Malina; Woon, Siew Fang; Kamal, Muhammad Farouk Zainol (School of Social Sciences, USM, 2017)
In everyday life in this modern and sophisticated world, many of us forget about the importance of life balance. Most of us have to prioritize the work of the family to meet the needs of the day. This study aims to investigate the factors affected the work-life balance among academician in University Utara Malaysia. This study is very important because if the employee is productive, they will bring the vast transformation into the Educational Institutions and individual levels. Currently, a few literature shows the study is not widely explored in Malaysia yet and many studies of work-life balance have been carried out in western country. Therefore, this study takes an opportunity and also initiated to fill the gap by conducting and explore towards which factors that ideally affected the work-life balance among the academician at that one kind of public university in Malaysia. A study was implemented among academicians in UUM based on the available factors that discovered in the literature and from the experts. The data collections were done through survey. The method that we used in the study is Mann Whitney Test and the Spearman correlation since the data is not normal. The finding showed it is no different in the work-life balance between male and female academician. Meanwhile, the correlation analysis showed that several factors such as top management, work environment, family, and friends are highly correlated to each other. This study may provide an initial overview of the factors affecting the work-life balance and provide an awareness of this among academicians.